Isolation and Structural Analysis of Active Antioxidant Phenolic Compounds from Elephantopus mollis Kunth - Verawati Verawati; Almahdy Almahdy; Febriyenti Febriyenti; Deddi Prima Putra (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Elephantopus mollis is a common weed found in West Sumatra, known for its diverse traditional uses and rich phytochemical content. This study aimed to isolate phenolic compounds and evaluate the antioxidant activity of the polar extract of E. mollis herb. The polar extract was obtained through successive extraction using solvents of increasing polarity. Separation of the polar extract was carried out using Amberlite XAD-4 resin chromatography with methanol and water eluents, followed by isolation through silica gel column chromatography using a step-gradient polarity elution system. The separation and isolation processes were monitored by thin-layer chromatography (TLC). Total phenolic content was determined by the Folin–Ciocalteu method, while antioxidant activity was assessed using the DPPH radical scavenging assay. Structural identification of the isolated compound was performed using UV-Vis, IR, NMR, and LC-MS spectroscopic techniques. Subfraction D of the polar extract exhibited a high phenolic content of 618.06 ± 3.38 mg GAE /g. From subfraction D, a phenolic compound designated D3a was isolated as a yellowish-white powder (95.30 mg) with an Rf value of 0.64, producing a dark blue color upon reaction with 10% FeCl₃. The antioxidant activity of compound D3a was classified as very strong, with an IC₅₀ value of 12.42 ppm. Based on physicochemical characterization, compound D3a was identified as caffeic acid with a molecular formula of C₉H₈O₄ and a molecular weight of 180.049.